Arbitrating Intellectual Property Disputes in India. Issue 2 (December 2019) - Mathew, Daniel
Recent years have witnessed enhanced utilisation of varied means of alternative dispute resolution to resolve a variety of disputes. While many areas have seamlessly adapted and internalised such extension, intellectual property disputes continue to offer stubborn resistance. This is because on the one hand intellectual property represents substantial business asset, while on the other it is an outcome of a carefully constructed public policy. The tension between the two viewpoints has a profound effect on how intellectual property disputes are understood and resolved. As a result, jurisdictions, world over, including India, have struggled to suitably respond to concerns emanating from private adjudication (in particular use of arbitration), to resolve public policy issues (such as disputes pertaining to intellectual property). This article attempts (a) a critical appraisal of the efforts to arbitrate intellectual property disputes in India, (b) identify and analyse legal roadblocks to such attempts including contradictory approaches adopted by Indian courts and (c) finally, undertake an evaluation of a possible compromise that enables arbitration of intellectual property disputes in India.